2015
DOI: 10.1039/c4ra11597j
|View full text |Cite
|
Sign up to set email alerts
|

Nano-heat-sink thin film composite of PC/three-dimensional networked nano-fumed silica with exquisite hydrophobicity

Abstract: Efficient utilization of fumed silica with thermoset resins had been investigated for high temperature applications, which led to extensive exploration of newer materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…In addition, the IL coating on the silica surface could have served as a protective layer to hinder further silica aggregation; this enabled a higher char yield and superior thermal stability in the nanocomposites. The increased yield and retention of this insulative char improved the ablator properties, prevented the heat flux from reaching the virgin material, and had a positive effect on the flame retardancy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the IL coating on the silica surface could have served as a protective layer to hinder further silica aggregation; this enabled a higher char yield and superior thermal stability in the nanocomposites. The increased yield and retention of this insulative char improved the ablator properties, prevented the heat flux from reaching the virgin material, and had a positive effect on the flame retardancy …”
Section: Resultsmentioning
confidence: 99%
“…The new era of developments in nanotechnology makes a strong case for articulating high‐thermal‐performance RF‐based ablative nanocomposites modified with an eloquent nanofiller for the benign interface zone between the polymer and nanoparticles. We selected fumed silica (FS) for this study, as it has the ability to chemically connect with polymer precursors and their functional groups and renders excellent thermal insulation properties in composites . The aim of this study was to elucidate the interfacial chemistry and related structure–property relationship issues for tailoring FS–RF interfacial interactions with enhanced thermal ablative properties to allow these materials to be used in thermal ablative applications where the containment and suppression of high‐thermal‐heat‐flux threats to humans, equipment, and structures is of paramount importance .…”
Section: Introductionmentioning
confidence: 99%
“…Pryde et al . have demonstrated that polycarbonate under the condition of humidity and temperature is conducive to the rapid hydrolysis if it do not contain hydrolytic stabilizers 12 , 13 . In another study Devis et al .…”
Section: Introductionmentioning
confidence: 99%
“…The modification via surface chemistry requires regulation of surface tension between oils (30 mN/m), and organic solvents (18.4 mN/m), and water (72.8 mN/m), thereby allowing only oil/solvent absorption but avoiding water wetting [2,10,12,16]. In present study, the authors have utilized engineering polycarbonate (PC) polymer for oil recovery, as it is mechanically strong (izod impact strength = 600-850 J/m), thermal stability (up to 350 °C), ability to facilitate solution formation, and maintaining its structural rigidity up to its high glass transition temperature (140 °C) [17][18][19][20][21][22]. The activated charcoal was utilized in conjunction with PC polymer, since it exhibits functionalized surface encompassing functional groups like C=O, -CO 3 , O-H, and C-O which facilitates bonding with polymer matrix, and is readily available in commercial market at low cost [23,24].…”
Section: Introductionmentioning
confidence: 99%